Adiposopathy and Obesity Paradox - Indriyanti Rafi Sukmawati; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Obesity has reached global epidemic proportions in both adults and children and is associated with numerous comorbidities, including hypertension, type 2 diabetes mellitus (T2DM), dyslipidemia and major cardiovascular diseases (CVD).CONTENT: Adiposity may cause adipocyte and adipose tissue anatomic and functional abnormalities, termed adiposopathy (adipose-opathy) or